Regulatory effect of phosphorus and nitrogen on nodulation and plant performance of leguminous shrubs. Issue 1 (9th August 2019) - Míguez-Montero, M A; Valentine, A; Pérez-Fernández, M A
Abstract: The impact of phosphorus (P) nutrition on plant growth, symbiotic N2 fixation, and phosphorus and nitrogen use and their assimilation was investigated in four leguminous plants of the genus Cytisus . Plants inoculated with Rhizobium strains isolated from plants of the four species growing in the wild were crop under controlled conditions in soils with either low P (5 µM) or high P (500 µM). The experiment was replicated in the presence and absence of plant irrigation to test for the effects of drought stress of inoculated and non-inoculated plants under the two P levels of fertilization. P-low treatments increased nodule production while plant biomass and shoot and root P and N contents were maximum at sufficient P. The reduction of P in the soil clearly induced biological nitrogen fixation and greater phosphorus and nitrogen uptake efficiencies, as shown by the total N and P accumulated in plants. Similarly, distinct tolerances to drought support this idea. Cytisus balansae had the lowest tolerance to water scarcity. Cytisus multiflorus and Cytisus scoparius were the most resistant species to drought, with this resistance enhanced in the inoculated plants. In the four species, the inoculation treatment clearly enhanced N-use efficiency, whereas P-use efficiency was greater in the non-inoculated plants in the irrigated treatment. With a P-induced demand for N, the plants nodulated prolifically and increased N supply from biological fixation. The physiological basis for N2 -fixing C . scoparius and C. striatus maintaining growth at low P supply and responding to greater P supply is through balanced acquisition of P and N for plant demand. Native shrubby legumes are key species in natural ecosystems due to their capability to increase the net N budget in plants and soils and because they modulate the phosphorus availability. Four legumes in the genus Cytisus either native to or commonly represented in the Iberian Peninsula proved to be able shift their N use depending on the soil P availability and on the interactions established with their Bradyrhizobium symbionts. In the four species the inoculation treatment clearly enhanced N-use efficiency and drought tolerance, whereas P-use efficiency was greater in the non-inoculated plants in the irrigated treatment.